Nasal Stimulation Response in Neurologically Normal Dogs and Cats - Tomás Elvira; Tim Sparks; Julien Guevar; Vicente Aige; Rodrigo Gutierrez‐Quintana; Josep Brocal (Journal of Veterinary Internal Medicine)
ABSTRACT Background The range of normal responses to nasal stimulation (NSR) observed in neurologically intact dogs and cats has not been reported. Hypothesis/Objectives Report the responses range while performing NSR in neurologically normal dogs and cats. Animals Twenty dogs and twenty cats, all neurologically normal. Methods Prospective descriptive study. Nasal stimulation response testing was performed four times in each animal. Responses to NSR were recorded and described. Neuroanatomical cadaveric evaluation was then performed to attempt to correlate the responses with anatomy. Results Withdrawal of the head was the most common response observed in both dogs and cats; it was present in all animals and during 150/160 stimulations. Other observed responses included lip lick response (39/40 animals and in 121/160 stimulations) and startle response (17/40 animals and in 34/160 stimulations). The latter was present in cats significantly (p = 0.026) more often (8/80 of stimulations in dogs and in 26/80 of stimulations in cats). The location of the examination (home vs veterinary hospital), stress, or covering the eyes did not significantly affect the responses. Conclusion and Clinical Importance Relevance Withdrawal of the head is a consistent response, but in its absence, looking for lip lick or a startle response could support the normal function of the pathway.